Digital Literacy Integration Model in Social Studies Education in the 3T Region: A Literature Review - Yandri Yusuf Cornelis Hendrik (STKIP Taman Siswa Bima, 2025)
The gap in access to technology and low digital literacy are fundamental problems in education in the 3T (Disadvantaged, Frontier and Outermost) regions. This research aims to formulate methods and strategies for the integration of digital literacy in social studies learning in the 3T regions. This research is motivated by the gap in access to information in each region, low digital competence and limited infrastructure in 3T areas. The research method used is a literature review with a qualitative descriptive approach to analyse various scientific sources and journals on digital literacy in social studies learning in 3T areas. The results of the study found five main components of the integration model namely access, content, pedagogy, participation and evaluation and digital literacy strategies that are relevant for 3T areas include teacher education and training, project-based learning methods, provision of local-based materials and content and evaluation of the learning process. Digital literacy in the 3T areas does not only look at the use of digital technology but the ability to critique digital content or information and ethics in using digital media.